An Emergent Change in Epidemiologic and Microbiological Characteristics of Bloodstream Infections in Adults With Febrile Neutropenia Resulting From Chemotherapy for Acute Leukemia and Lymphoma at Reference Centers in Chile, Ecuador, and Peru - Rabagliati, R (2024)
Background. Febrile neutropenia is a life-threatening condition commonly observed in patients with hematologic malignancies. The aim of this article is to provide updated knowledge about bloodstream infections in febrile neutropenia episodes within the Andean region of Latin America. Method. This retrospective study was based in 6 hospitals in Chile, Ecuador, and Peru and included adult patients with acute leukemia or lymphoma and febrile neutropenia between January 2019 and December 2020. Results. Of the 416 febrile neutropenia episodes, 38.7% had a bloodstream infection, 86% of which were caused by gramnegative rods, with Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa being the most frequently identified bacteria. K pneumoniae isolates were more frequently resistant than E coli to cefotaxime (65% vs 39.6%), piperacillintazobactam (56.7% vs 27.1%), and imipenem (35% vs 2.1%) and were more frequently multidrug resistant (61.7% vs 12.5%). Among P aeruginosa, 26.7% were resistant to ceftazidime, piperacillin-tazobactam, and imipenem, and 23.3% were multidrug resistant. Overall 30-day mortality was 19.8%, being higher with vs without a bloodstream infection (26.7% vs 15.3%, P = .005). Fever duration was also significantly longer, as well as periods of neutropenia and length of hospital stay for patients with bloodstream infection. Additionally, the 30-day mortality rate was higher for episodes with inappropriate vs appropriate empirical antibiotic therapy (41.2% vs 26.6%, P = .139). Conclusions. Considering the high rates of bacteria-resistant infection and 30-day mortality, it is imperative to establish strategies that reduce the frequency of bloodstream infections, increasing early identification of patients at higher risks of multidrug bacteria resistance, and updating existing empirical antibiotic recommendations.